Enterprise Architecture of the Basic Banking Feature for a New Challenger of Digital Banking in Indonesia - Sentosa, Steve; Indrajit, Richardus Eko; Dazki, Erick (Sinkron : jurnal dan penelitian teknik informatika, 2024)
Digital transformation has significantly impacted Indonesia's banking industry, leading to the rise of digital banks that leverage technology for their operations, posing challenges to traditional banking models. This research investigates the implementation of enterprise architecture within the core features of digital banking in Indonesia, utilizing the TOGAF framework and Archimate modeling. The study's primary objective is to identify the core processes, challenges, and opportunities associated with managing the complex architecture of digital banks. Employing a qualitative methodology, data were gathered through in-depth interviews, direct observations, and a review of pertinent literature. The research identified three central processes in digital banking operations: deposits, time deposits, and loans. These processes were then modeled using the TOGAF framework and Archimate to align business strategies with operational activities more effectively. The SWOT analysis conducted highlights digital banks' strengths in operational efficiency, strategic partnerships, and innovation capabilities, while also recognizing weaknesses such as technological dependency and challenges in serving the less tech-savvy population. The study also identifies opportunities for product innovation, market expansion, and ecosystem integration. However, threats like regulatory changes, increased competition, and cybersecurity risks must be carefully managed. The research recommends adopting emerging technologies, enhancing third-party risk management, and improving customer data security and privacy to bolster digital banks' global competitiveness, operational sustainability, and service innovation.